Structural and EPR studies of Cu2+ ions in NaPO3 – Sb2O3 – CuO glasses - Franco, Douglas F. [UNESP]; Carvajal, Eduar E.; Donoso, José Pedro; Silva, Maurício A.P.; Sant'Ana, Antonio C.; Fares, Hssen [UNESP]; Magon, Claudio J.; Nalin, Marcelo [UNESP] (Elsevier, 2019)
In this work, glass compositions in the system NaPO3 - Sb2O3 – CuO (PSbCu) containing different concentrations of CuO and Sb2O3 were prepared through the melt - quenching methodology. Thermal, structural and optical properties of the PSbCu glasses were systematically studied by differential scanning calorimetry (DSC), X – ray powder diffraction (XRD) and Raman, UV–Visible and Photoluminescence (PL) spectroscopies, besides electron paramagnetic resonance (EPR) measurements. The DSC curves for all samples presented the glass transition phenomenon (Tg), while the XRD patterns showed the presence of an amorphous halo, which confirmed the glassy nature of all samples analyzed. UV–Vis spectra of the glasses showed a transparent window from 450 to 800 nm. The EPR signals intensities were investigated as a function of the copper concentration and Sb2O3 content in the (PySb0.5Cu) (20 ≤ y ≤ 80) and (PSb80xCu) (0.25 ≤ x ≤ 1.25) glasses. The EPR results showed that the increase of Sb2O3 concentration on the PySb0.5Cu glasses decreased the Cu2+ signals, which suggests the Sb3+ oxidizing to Sb5+, also transferring electrons to Cu2+ species to create the EPR a silent Cu+ specie. According to EPR parameters and PL spectra (excited at 380 nm) of PySb0.5Cu glasses, the ions Cu2+ ions were preferentially found in a distorted octahedral geometry, while Cu+ is in a square planar geometry according to the Jahn-Teller effect.
Keywords: Antimony glasses; Electron paramagnetic resonance; Optical properties